PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN PJBL PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS III SD N 067240 MEDAN TEMBUNG - Esrawati Haloho; Sri Wahyuni; Nona Alfira Lubis (STKIP Subang, 2024)
Improving thematic learning outcomes through the PJBL model for Class III students at SDN 067240 Medan Tembung. Pre-service PPG Follow-up Research for Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of North Sumatra, 2024. This research aims to describe: 1) Describe the application of the PjBL Model to improve student learning outcomes in Class III Indonesian language content. 2) Describe the increase in learning activity in students using the PjBL model in Indonesian Language content for Class III SDN 067240 Medan Tembung. This research is a type of Classroom Action Research (PTK). This research was carried out in 2 cycles, and each cycle held two meetings. The subjects of this research were 17 class III students at SDN 067240 Medan Tembung, which was carried out in the odd semester of the 2024/2025 academic year. The object of this research is learning outcomes in learning Indonesian using the PjBL Model. Research data collection techniques use observation, tests and documentation. The data analysis technique used in this research uses qualitative and quantitative data. The research results show that there is an influence of the Project Based Learning (PjBL) learning model with the peer lesson strategy on the learning outcomes of class III students at SDN 067240 Medan Tembung. This is evidenced by the percentage between pre-cycle, cycle I and cycle II which experienced a significant increase. The percentage in the pre-cycle was 35%, while in the first cycle it was 59%, then after the second cycle it increased to 85%.